Analisis Penyaluran Dana CSR pada PT Bank Sumut - Halim Afif Siregar; Khairina Tambunan; Marliyah Marliyah (ManBiz: Journal of Management and Business, 2023)
Companies that benefit from the business they run should not think about themselves, companies must also think about the community and the surrounding environment to provide a form of social responsibility or Corporate Social Responsibility (CSR). One of the regional owned enterprises (BUMD) of North Sumatra, namely: PT. Bank Sumut which holds a Corporate Social Responsibility program regularly every year with funds from CSR programs distributed to several sectors, such as the education, health, social and economic sectors. This research is qualitative in nature, to collect data and information obtained in this study is primary data collected from interviews at PT. Bank of North Sumatra, as well as secondary data collected from the annual report site at Bank of North Sumatra. Related data were analyzed using descriptive method. Data collection techniques were analyzed using interviews and questionnaires from the Head of CSR. The results showed that the process of channeling CSR funds for the Bank of North Sumatra was carried out by submitting CSR proposals which were funding in nature, namely funding for programs that had been submitted to the North Sumatra bank as programs that would be funded with CSR. government work forum teams as well as those directly submitted to the North Sumatra bank will then be analyzed and reviewed by the company. After the CSR funds are handed over to the beneficiaries, the program can be directly run in accordance with the activities that have been proposed in the previous work budget proposal and costs. And accountability reports by beneficiaries and re-verified by the North Sumatra Bank CSR team. Keywords: CSR (Corporate Social Responsibility), Bank of North Sumatra